2016
DOI: 10.1007/s11010-016-2762-6
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab’s effect on cognitive deficits induced by intracerebroventricular administration of streptozotocin in Alzheimer’s model

Abstract: Neuroinflammation plays pivotal roles in the pathogenesis of Alzheimer's disease (AD). IL-6 is pleiotropic cytokine which plays significant pathological role in inflammatory diseases and causes prolonged inflammation. Additionally, IL-6 activates microglia cells and enhances the accumulation of amyloid-β peptides. Moreover, IL-6 signal transduction is mediated by membrane-bound and soluble IL-6 receptors. Tocilizumab which is a humanized anti-human IL-6 receptor (IL-6R) monoclonal antibody binds to both of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Efficacy of another TNF-α inhibitoretanercept has been studied in Alzheimer's disease (Tobinick, 2012); however, a recent placebocontrolled, double-blind, phase 2 trial of subcutaneous etanercept demonstrated no significant changes in cognition, behaviour and global functioning (Butchart et al, 2015). Preclinical evidence also indicates that toclizumab, which is a monoclonal antibody inhibiting IL-6 signalling, might improve spatial memory and learning in Alzheimer's disease animal model (Elcioglu et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Efficacy of another TNF-α inhibitoretanercept has been studied in Alzheimer's disease (Tobinick, 2012); however, a recent placebocontrolled, double-blind, phase 2 trial of subcutaneous etanercept demonstrated no significant changes in cognition, behaviour and global functioning (Butchart et al, 2015). Preclinical evidence also indicates that toclizumab, which is a monoclonal antibody inhibiting IL-6 signalling, might improve spatial memory and learning in Alzheimer's disease animal model (Elcioglu et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…143 However, levels of inflammatory markers in COVID-19 patients may be lower than levels observed in secondary insults such as acute respiratory distress syndrome (ARDS) that could be associated with SARS-CoV-2 infection. 144 The interleukin (IL)-6 inhibitor, tocilizumab, reduces cognitive deficits in a mouse model of AD, 145 and IL-6 inhibitors are being studied in clinical trials for their efficacy in treating severe SARS-CoV-2 disease. 143 Long-term follow-up of these patients will enhance understanding of the role of IL-6 and SARS-CoV-2 in any subsequent neurodegeneration.…”
mentioning
confidence: 99%
“…Animal data suggest that tocilizumab is safe and effective for treatment of severe acute pancreatitis and associated acute lung injury [22]. Further, tocilizumab had neuroprotective effects in a model of Alzheimer's disease [23].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%